Agregação do solo e suas inter-relações com atributos físicos e químicos sob usos agrícolas no Semiàrido potiguar - Silva, Francisco Wellington Andrade da (Universidade Federal Rural do Semi-Árido, 2019)
The aggregation process is fundamental because of its close relationship with the structural quality of the soil. This research was developed in the Terra de Esperança Settlement project in Governador Dix Sept Rosado, in Rio Grande do Norte, in four areas: orchard area, corn and bean and watermelon and jerimum consortium area, and agroecological area, in the depths from 0-15 m, 15-30 m and 30-45 m. Samples with deformed and undeformed structure, collected in plastic bags, were collected and analyzed in the complex of the Soil, Water and Plant Analysis Laboratory of the Center for Agricultural Sciences of the Federal Rural University of Semiarid (LASAP-CCA-UFERSA). The analyzes were: silt, sand and clay, Soil Density (Ds), Total Porosity (PT), Gravimetric Humidity (UG) and Volumetric Humidity (UV); Geometric and weighted mean diameters (DMG, DMG). Chemicals were: EC, pH, PST, COT, phosphorus P, potassium K+, Ca2+), magnesium (Mg2+ ) and PST. The particle size was obtained by the pipette method. Dp analysis was performed by the volumetric balloon method. Undisturbed samples were collected using Uhland type apparatus and rings with dimensions of 0.05 m in height and 0.05 m in diameter. The UG was determined by the standard method, and then the UV was calculated. Total porosity, macro and microporosity, was used at 6 kPa, and microporosity by difference between total porosity and macroporosity. Field capacity (CC) was defined at the 33 kPa voltage representing the condition of clay soils. Permanent wilting point (PMP) at 1500 kPa voltage and available water was determined by the difference between CC and PMP. Aggregates performed by wet sieving method. The chemical attributes evaluated were: pH EC, TOC, by digestion of organic matter and exchangeable calcium Ca2+ , Mg2+, P, Na+ and K+ , and PST were calculated. Data were submitted to multivariate statistical analysis. Ca2+ and Mg+ 2 showed an interrelation with the structural attributes. Group I was formed by the ACMJ environment in all layers, highlighting the structural aggregate stability and TOC, reflections of the structural conditions under conventional tillage; fourth, group II was distinguished by all physical and chemical attributes; a direct reflection of the interrelationships between the physical and chemical attributes culminated in the soil structuring process and the multivariate was efficient in distinguishing the environments, selecting the attributes that presented the highest factor loadings.
Monografia
Keywords: Manejo agroecológico; Caatinga; Semiárido; Agregação; Estrutura; CIENCIAS AGRARIAS::AGRONOMIA